Analisis Yuridis Syarat Izin Poligami Menurut Hukum Posistif Indonesia (Studi Kasus Penetapan Nomor 26/Pdt.P/2022/PN Bli) - Ni Luh Sintya Damayanti; I Nyoman Putu Budiartha; I Nyoman Subamia (Fakultas Hukum Universitas Warmadewa, 2024)
Marriage in Indonesia adheres to the principle of monogamy, which means having only one wife, but in fact along with the times there is the fact that a husband can have more than one wife or what is known as polygamy. This research was conducted with the aim of describing how the requirements for the validity of a polygamy permit based on the provisions of the Marriage Law and how the Judge's consideration in deciding a polygamy permit case that does not meet the requirements in the Marriage Law case study of determination number 26/Pdt.P/2022/PN Bli. This research uses normative legal research methods as well as statutory, conceptual, and case approaches. The results of this study indicate that a husband is given the leeway to have more than one wife or polygamy if he fulfills the requirements listed in Articles 4 and 5 of Law Number 1 Year 1974 concerning Marriage. The results of this study indicate that the Judge's decision to grant permission to have more than one wife or polygamy that does not meet the applicable requirements, the Judge sees the cultural point of view, Hindu beliefs, and the best interests of the child.